If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + 5x + 6 = 0 Multiply x * x x2 + 5x + 6 = 0 Reorder the terms: 6 + 5x + x2 = 0 Solving 6 + 5x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + x)(2 + x) = 0Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-3, -2}
| x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 | | (2x^2-x+7)+(3x^2+x-9)= | | x(x)-7x-8=0 | | (40x)+(20*1.5x)=1625 | | 2-4y=4-5y | | 7y+3=6y-2 | | 6.4-2.1x=-77.4 | | x+y^2=0 | | 5-5x+8+2x+4x-4=3+2*5 | | x=1-y^2 | | 48=12-6n | | -2.3+m=-2.3 | | x-3/2=7/4 | | r+3.5=8 | | m(m)+6m-9=0 | | 20=10-5p | | 3(x)(x)-2x-5=0 | | (5x-5)(5x-5)= | | 15-39=-9 | | (7x^3-9x^2+5x)-(2x^2+3+6)= | | 2(x)(x)-3x-8=0 | | 40*12x=60x | | 25=7+3x | | 36x^2-12x+2=0 | | 5z-34=4z+4 | | cd^4-c^2d^6= | | -8(t-4)-(t+1)=5 | | 14-2y=-8 |